ARE HIGHER WAGES GOOD FOR BUSINESS? AN ASSESSMENT UNDER ALTERNATIVE INNOVATION AND INVESTMENT SCENARIOS. (4th July 2018) - Caiani, Alessandro; Russo, Alberto; Gallegati, Mauro
Abstract : This paper aims at investigating the interplay between inequality, innovation dynamics, and investment behaviors in shaping the long-run patterns of growth of a closed economy. By extending the analysis proposed in Caiani et al. [(2018) Journal of Evolutionary Economics], we explore the effects of alternative wage regimes under different investment and technological change scenarios. Experimental results seem to de-emphasize the role of technological progress as a possible source of greater inequality. Overall, simulation results are consistent with the predominance of a wage-led growth regime in most of the scenarios analyzed: A faster growth of low- and middle-level workers' wages, relative to managers', generally exert beneficial effects on the economy and allows to counteract the labor-saving effects of technological progress. Furthermore, a distribution more favorable to workers does not compromise firms' profitability, but rather strengthen it by creating a more favorable macroeconomic environment, which encourages further innovations, stimulates investment, and sustains economic growth.